The regulating mechanism of MgCO3·3H2O whisker growth orientation with the presence of SDS. Issue 42 (December 2020) - Geng, Xi; Lv, Li; Zhang, Tao; Tang, Shengwei
Graphical abstract: Highlights: MgCO3 ·3H2 O whisker with high aspect ratio of 40 was successfully prepared. The regulating mechanism of MgCO3 ·3H2 O whisker growth orientation was proposed. The adsorbed (CH3 (CH2 )11 -OSO3 )2 Mg on the [100] crystal plane hinders the growth of the crystal plane in the [100] direction. MgCO3 ·3H2 O whisker is oriented to grow in the [010] direction with high aspect ratio. Abstract: CO2 mineralization is an effective route to reduce CO2 emission. But the commercialization of CO2 mineralization process is impeded by the poor or even negative profit. MgCO3 ·3H2 O whisker was prepared by indirect CO2 mineralization of MgSO4 -(NH4 )2 CO3 in the presence of Sodium Dodecyl Sulfate (SDS) to improve the profit. MgCO3 ·3H2 O whisker with an average length of 40 μm, average diameter of 1 μm, and aspect ratio as big as 40 was successfully prepared with the presence of SDS. SEM, AFM, XRD and TGA were used to characterize the morphology and structure of MgCO3 ·3H2 O whisker, and XPS was used to characterize the compositions of MgCO3 ·3H2 O crystal planes. The regulating mechanism of MgCO3 ·3H2 O whisker growth orientation was studied systematically. The SDS ionizes CH3 (CH2 )11 -OSO3 - in the solution, and then combines with the active site Mg 2+ complex on the crystal plane in the [100] direction. The (CH3 (CH2 )11 -OSO3 )2 Mg faces the liquid phase with the hydrophobic group CH3 (CH2 )11 -, which separates the [100] direction from the liquid phase, hindering the growth of the [100] direction crystal plane. Therefore, MgCO3 ·3H2 O whisker is oriented and grows easily on the [010] direction with high aspect ratio.